Growing empathy through art therapy, life story, and relationships: experiential learning in adult day services - Peeples, L. Blake; Thompson, Benjamin C.; Tucker, Jackie B.; Smith, LaDerrick; Brown, Amy; Carden, Keisha D.; Halli-Tierney, Anne; Duncan, Angel C.; Aggarwal, Neelum T.; Allen, Jessica Y.; Allen, Rebecca S.; Potts, Daniel C. (Frontiers in Psychology, 2024)
Empathy is a fundamental element of high-quality healthcare, though it has been shown to be in decline among medical students and residents (Yu et al., 2022). Appeals have therefore been made for the development of evidence-based empathy-enhancing experiential learning and training models. Bringing Art to Life (BATL) is a service-learning program designed within experiential learning pedagogy for psychology and pre-healthcare students in which intergenerational relationships are fostered with people with dementia through art therapy and life story/narrative at a community-based adult day services center. In this sequential mixed methods study, quantitative data were collected via electronic surveys of students in this course compared with students in didactic introductory psychology or psychology and aging courses, followed by qualitative content analysis of weekly BATL student journals submitted as part of their course requirements. Survey measures included empathy, mindfulness, positive and negative affect, future time perspective, and attitudes towards older adults and working with people with dementia. Within-subjects analyses of variance revealed increases in empathy and positive affect, broadened time perspective, and improved attitudes toward older adults and people with dementia among students in the BATL course compared with other undergraduate students. Analysis of BATL student journals supported and deepened understanding of these findings, with themes including attitude change, relationship building fostering existential awareness and self-development, art fostering social interactions, and perceived program effectiveness. BATL strongly supports increased empathetic attitudes and decreased stigma of aging in psychology and pre-healthcare students. Intergenerational expressive arts-based programs should be implemented in healthcare education.